Integrating Fiqh Al-‘Ibadat and Qur’anic Learning in Primary Islamic Education: A Comparative Study of Indonesia, Malaysia, Pakistan, and Nigeria - Moh. Syarif Hidayat; Hisam Ahyani; Naeli Mutmainah; Siti Nurohmah; Iryansyah Iryansyah; Attabik Hasan Ma’ruf; Anisa Nurul Amalia; Nurlailatul Nikmah; Ihwanul Muadib; Mowafg Masuwd (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2026)
Primary Islamic education plays a crucial role in shaping children’s religious understanding, moral character, and everyday worship practices. However, the teaching of fiqh al-‘ibadat and Qur’anic learning often remains fragmented, with theoretical instruction separated from practical application across different educational contexts. This study aims to compare how these two domains are integrated in primary Islamic education in Indonesia, Malaysia, Pakistan, and Nigeria, and to identify pedagogical patterns that support holistic student development. A qualitative comparative multiple-case design was employed using document analysis, semi-structured interviews with teachers and school leaders, and classroom observations across selected schools in the four countries. Data were analyzed thematically to identify recurring similarities, differences, and contextual factors influencing instructional practice. The findings show two dominant models. Indonesia and Malaysia demonstrate more structured integration between conceptual learning, worship practice, and moral reflection through curriculum guidance and teacher preparation. In Pakistan and Nigeria, instruction places stronger emphasis on ritual performance and memorization, while conceptual and reflective dimensions depend largely on teacher initiative. Across all contexts, teachers face common challenges in simplifying abstract religious concepts for young learners. The study concludes that effective primary Islamic education requires balanced integration of knowledge, practice, and values. It implies that curriculum reform, teacher professional development, and contextual learning resources are needed to strengthen holistic Islamic education in diverse institutional settings.